The physiological comparison revealed the importance of focusing anti-oxidation function during the peak laying stage in hens based on multi-omics analysis - Yumeng Wang; Xi Sun; Xiaoying Liu; Chaohui Wang; Zhouzheng Ren; Xin Yang; Xiaojun Yang; Yanli Liu (Animal Nutriomics)
With the increase in egg production rate and the coming of peak laying period, some metabolic disorders usually emerge in layers. The current study was conducted to compare the physiological difference between the early laying stage (around 30% laying rate) and peak laying stage (more than 95% laying rate) of laying hens based on hepatic transcriptome, serum metabolomics and caecal microbiota. The results showed that the egg weight and yolk weight were significantly higher in peak laying hens. Further, serum malondialdehyde and total bile acid concentrations were higher, but total anti-oxidant capacity, total bilirubin and low-density lipoprotein cholesterol (LDL-c) concentrations were significantly lower in peak laying hens. Hepatic transcriptome analysis identified 540 up-regulated and 269 down-regulated genes. Consistently, fatty acid biosynthesis, PPAR and insulin signalling pathways were significantly enriched. Subsequently, the result of serum metabolomics identified 74 up- and 77 down-regulated metabolites. Among down-regulated metabolites, hesperetin, apigenin and betaine related to anti-oxidant function were down-regulated. In addition, western blotting result showed BCL2 and p53 proteins expressions were decreased in the peak laying period, whereas hepatic CEBPα protein level was increased. On the other hand, gut microbiota analysis revealed that Chao index was decreased in peak laying hens. And the LEfSe analysis showed the dominant microflora including Ruminococcus, Oxalobacter, Paracoccus and so on was found in peak laying hens. These findings indicated that the hepatic lipid metabolism of peak laying hens is enhanced and the decline in anti-oxidant performance of hens also implies its importance during the early stage of egg production.